Informational Security: Organizational and Legal Aspects - Zhatkanbaeva, A; Yerezhepkyzy, R; Salyhbaeva, A (Farabi Journal of Social Sciences, 2016)
In the advanced countries of the world the development of information infrastructure and information environment is under State control. Another important issue in the field of information security is to reduce information independence, although its achievement in the modern world is a utopia. Global communication reduces the role of the State at the national information field. Impossible or very expensive to ensure State control over the flow of information.Multinational companies often surpass national thanks to technical equipment and greater media audience. In order to ensure the availability of cellular communication to the general public, the Commission on human rights had recommended to the Government of Kazakhstan to take effective measures to promote competition in the provisionof services of cellular communication in Kazakhstan and reduction of cellular communication services. Positive experience of a number of countries. For example, the Government of Japan, Singapore, Malaysia has reduced prices on the Internet and it service providers. The most serious problem is the question of the definition of the role and place of Kazakhstan in the world that is largely determined by the level of information, awareness and information protection.